Extensive fishing Carrying Capacity oftheFPK Reservoir, Riau University Based on Chlorophyll-a - Ayunanda Mustika Sari; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT               Carrying capacity is defined as the ability of aquatic environment to support the life of organisms in that area. A study aims to assess the extensive fishing carrying capacity of the FPK reservoir based on primary productivity (chlorophyll-a content), has been conducted in November-Desember 2018. There were 3 stations, namely Station 1 (inlet area), Station 2 (in the middle of the reservoir) and Station 3 (outlet area). Water quality parameters measured were temperature, transparency, pH, dissolved oxygen, CO2, nitrate, phosphate, and chlorophyll-a concentration. The concentration of chlorophyll-a indicates that the extensive fishing’s carrying capacity of the reservoir was 0.31 tons/year. Water quality parameters were as follows: transparency ranges from 66.7-106.8 cm, temperature   28-29°C, pH 6, dissolved oxygen 2.52-2.66 mg/L, free CO2 6.7-9.83 mg/L, nitrate 0.3667-0.4118 mg/L, phosphate 0.2080-0.2154 mg/L, and concentration of chlorophyll-a was 12.78-15.96 µg/L. Keywords:Carrying capacity, Produktivitas Primer, Fitoplankton, Reservoir, Water quality